Analisis Potensi Pengembangan Kawasan Wisata Pantai Lumpue Kota Parepare - Hairuddin Hairuddin; Muhammad Fahreyza Latanro; Rahmad Rahmad; Imam Fadly; Mithahul ulum; Adnan Adnan (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Development study of the planning strategy of the Lumpue Beach tourism area located in Parepare City, South Sulawesi. The main focus of the study is to identify existing attractions, infrastructure conditions, and apply development planning strategies with a SWOT approach. Lumpue Beach is a coastal area that has interesting ecological and aesthetic values, but has not been exploited as a tourist destination. The approach used in this study is qualitative descriptive, which is complemented by quantitative data obtained through surveys, interviews, secondary as well as primary data from the concerned institutions. The analysis shows that Lumpue Beach has great potential with its ecological, natural beauty, local culture, and easy access. Its notable weaknesses include: lack of supporting facilities, environmental cleanliness, and absence of government and private sector coordination to plan the development of the area. As for the opportunity for increased interest in marine tourism, as a strategic area of Parepare City, there is also the support of local tourism agencies, such as Pokdarwis. Then the threats that must be addressed, including: environmental pollution and exploitation of areas there is no coordination of government and private parties. of this study include the sustainable and integrated development of Pipda and the urban spatial plan of Parepare, the improvement of facilities and infrastructure, the involvement of local communities, as well as the promotion of Panatai Tourism destination through digital platforms. The findings of this study are expected to serve as a reference for the City government and stakeholders in planning sustainable Lumpue Beach tourism area development strategies integrated with Parepare municipal regulations.